2018
DOI: 10.4136/ambi-agua.2084
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a solar still in destroying virus and indicator bacteria in water for human consumption

Abstract: Natural water distillation can destroy and/or inactivate microorganisms that are sensitive to heat and ultraviolet radiation (UV). This method is currently used to provide fresh water in ships and in the desalination of brackish water. For the development of this research, a pilotscale solar still was built and installed in the southern region of Brazil, in order to assess its efficiency in water disinfection, which was based on the most probable number (MPN) of total coliforms and Escherichia coli, in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
2
0
4
Order By: Relevance
“…Portanto, este estudo confirma que existem certas temperaturas (aquelas na faixa microbiana ideal de crescimento) que pode prejudicar a desinfecção solar. Nascimento et al (2018) construíram um destilador solar em escala piloto para verificar a eficiência do equipamento (Figura 8) na desinfecção de água. A destilação natural da água pode destruir e/ou inativar microrganismos que são sensíveis ao calor e a radiação UV-A.…”
Section: Resultsunclassified
“…Portanto, este estudo confirma que existem certas temperaturas (aquelas na faixa microbiana ideal de crescimento) que pode prejudicar a desinfecção solar. Nascimento et al (2018) construíram um destilador solar em escala piloto para verificar a eficiência do equipamento (Figura 8) na desinfecção de água. A destilação natural da água pode destruir e/ou inativar microrganismos que são sensíveis ao calor e a radiação UV-A.…”
Section: Resultsunclassified
“…Recent work on the reliability of solar stills for wastewater treatment found that 90% of the virus can be removed by heating the WWTP effluent to 70 °C and denaturing proteins at high temperatures [17] , and the pilot-scale solar could remove 4.5 log (99.997%) of HAdV-5 in the distillation process [222] . Furthermore, the emergence of nanotechnology improved the distillation mechanism greatly, and might help alleviate water issues by solving the technical challenges that removing viruses [223] , creating potential avenues for addressing the virus concerns via the combination traditional desalination and emerging materials.…”
Section: Removal Trends Of Viruses In Different Wwtp Unit Processesmentioning
confidence: 99%
“…O processo respiratório é aeróbio ou anaeróbio facultativo, fermentando lactose e produzindo gás a uma temperatura de 35ºC, entre 24 e 48 horas. Estes coliformes fazem parte da microbiota natural do trato gastrointestinal de alguns animais endotérmicos, incluindo o homem (Funasa, 2013;Mueller & Tainter, 2022).…”
Section: Introductionunclassified
“…No entanto, a presença e a quantidade de colônias são indicativos da qualidade higiênico-sanitária de um produto (Silva & Melo, 2021). Por fazer parte da flora natural do intestino (bactéria comensal), os coliformes não são patogênicos; porém, quando encontrada fora do trato intestinal, algumas linhagens ou a proliferação destes microrganismos podem ser a causa de doenças intestinais e extraintestinais em humanos, como as infecções do trato urinário e a pneumonia (Lopes Neto et al, 2021;Mueller & Tainter, 2022).…”
Section: Introductionunclassified